Entangled education: Technology and pedagogy in universities as a mash up - Thestrup, Klaus; Shumar, Wesley; Robinson, Sarah (Proceedings of the International Conference on Networked Learning, 2026)
The paper suggests that a pedagogical advance in universities could be to set up university courses where the digital is integrated more organically into courses and not seen as a separate thing. Drawing on work in postdigital education we suggest that higher education is still trapped in a binary where online courses are seen as analogues, and copies of an original face-to-face course. This vision is historically connected to the early days of the internet where online communities were seen as separate from face-to-face communities in the literature on the internet. The world has moved on, as technology has advanced, to see that every aspect of our lives involves a digital component and the simple separation of online and offline no longer fits with the entangled reality that people live. Many scholars refer to this moment as postdigital. And they are careful to say that postdigital does not mean that we are past the digital, but rather that the digital is part of all life. It is somewhat ironic that universities, in their practice, have not kept up with these changes though the scholars have. This means moving beyond learning management systems (LMS) and integrating numerous forms of digital technology. The LMS can still be part of a university course, but it is one digital tool among many. And the binary between online and offline would be challenged and the hybrid might be a more useful term than online. This could lead to an entangled education where space and time are transformed, as well as creating new forms of interaction and new avenues for communication in the learning process. In such a context, university students could engage actively in their own learning and be provided with spaces to integrate their ideas into the process. The paper shares some examples of these courses referring to them as experimenting communities. In these examples we show how the new forms of interaction and the transformed spaces in which these interactions occur increase opportunities for students to make sense out of the material they are learning and to see learning connected to real world problems and solutions.